1858-1859 N.C. Sess. Laws 35-36 - (:unkn) unknown (My University, 1858)
Pub. Laws, ch. 25, § 27, pt. 15: Imposed a tax of one dollar and twenty-five cents on every dirk, Bowie-knife, pistol, sword cane, dirk-cane, and rifle cane.
Keywords: TAX - PROPERTY OR SALES